Quantifying the fraction of cirrhosis attributable to alcohol among chronic hepatitis C virus patients: Implications for treatment cost‐effectiveness1. Issue 2 (8th January 2013) - Innes, Hamish A.; Hutchinson, Sharon J.; Barclay, Stephen; Cadzow, Elaine; Dillon, John F.; Fraser, Andrew; Goldberg, David J.; Mills, Peter R.; McDonald, Scott A.; Morris, Judith; Stanley, Adrian; Hayes, Peter; et al.
Abstract A substantial baseline risk of liver cirrhosis exists for patients with chronic hepatitis C virus (HCV) infection. However, the extent to which this could be driven by heavy alcohol use is unclear. Therefore, our principal aim was to determine the fraction of cirrhosis attributable to heavy alcohol use among chronic HCV patients attending a liver clinic. The study population comprised chronic HCV patients who had attended one of five liver clinics in Scotland during 1996‐2010 and had (1) remained in follow‐up for at least 6 months, (2) acquired HCV through either injecting drugs or blood transfusion, and (3) an estimated date of acquiring infection. Predictors of cirrhosis were determined from multivariate logistic regression. Regression parameters were used to determine the fraction of cirrhosis attributable to heavy alcohol use. Among 1, 620 patients, 9% were diagnosed with cirrhosis, and 34% had ever engaged in heavy alcohol use (>50 units/week for a sustained period). Significant predictors of cirrhosis were age, duration of infection, and ever heavy alcohol use. The fraction of cirrhosis attributable to ever heavy alcohol use was 36.1% (95% confidence interval [CI]: 24.4‐47.4). Moreover, among patients who had ever engaged in heavy alcohol use specifically, this attributable fraction exceeded 50% (61.6%; 95% CI: 47.0‐72.2). Conclusions: A substantial proportion of patients with chronic HCV develop liver cirrhosis as a consequence of heavy alcohol use. This has not been adequately acknowledged by cost utility analyses (CUAs). As such, estimates of cost‐effectiveness may be exaggerated. Thus, these data are important to guide forthcoming CUAs in terms of taking better account of the factors leading to cirrhosis among patients with chronic HCV. (HEPATOLOGY 2013)